Pułapki w stosowaniu nieostrych pojęć w badaniach jakościowych (z doświadczeń badawczych realizatorów projektu MKiDN) = Traps in the application of mild concepts in quality research (from the research experience of MKiDN project executors) - Idzikowski, Bogdan; Słowińska, Sylwia (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Quality research have been equipped with the so called "soft" conceptuality. Their originality and innovativeness consist in the avoidance of creating precise pre-assumption, building a theoretical and methodological model, parameterizing data and testing hypotheses. Quality researchers more frequently refer to the language of metaphors, reading hidden meanings, understanding the sense, all these given to different phenomena by researched subjects.
Keywords: kultura lubuska; inicjatywy kulturalne; województwo lubuskie; badania jakościowe